2000
DOI: 10.1115/1.1318941
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation of Intraventricular Flow and Pressure Gradients During Diastole

Abstract: A two-dimensional axisymmetric computer model is developed for the simulation of the filling flow in the left ventricle (LV). The computed results show that vortices are formed during the acceleration phases of the filling waves. During the deceleration phases these are amplified and convected into the ventricle. The ratio of the maximal blood velocity at the mitral valve (peak E velocity) to the flow wave propagation velocity (WPV) of the filling wave is larger than 1. This hemodynamic behavior is also observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 22 publications
9
62
1
Order By: Relevance
“…This concept is illustrated in Fig. 3 Vierendeels et al [46] , using a numerical model, confirmed this close relationship between the position of the vortex core and the position of the maximum velocities along the base-apex axis.…”
Section: Travelling Vortices and Colour M-mode Doppler Echocardiograpmentioning
confidence: 63%
See 3 more Smart Citations
“…This concept is illustrated in Fig. 3 Vierendeels et al [46] , using a numerical model, confirmed this close relationship between the position of the vortex core and the position of the maximum velocities along the base-apex axis.…”
Section: Travelling Vortices and Colour M-mode Doppler Echocardiograpmentioning
confidence: 63%
“…Phase II is the propagation of the maximum velocity that can be associated with the propagation of a vortex ring as described before. The biphasic filling pattern is observed in vitro [45] , in numero [46] and in vivo [30,41,49,50] .…”
Section: S De Mey Et Almentioning
confidence: 81%
See 2 more Smart Citations
“…An intriguing aspect of the left heart dynamics is the hypothesised occurrence of diastolic vortices within the ventricular chamber. Their presence and properties have been analyzed in theoretical (Reul et al, 1981;Wieting & Stripling, 1984), experimental (Steen & Steen, 1994), and numerical models (Vierendeels et al, 2000;Baccani et al, 2002 ), and introduced also in medical observations (Kim et al, 1994;Kim et al, 1995;ab Kilner et al, 2000). The presence of vorticity makes the fluid dynamics approach relevant for the understanding of the possible patterns and their relation with the mechanical properties of the surrounding tissues.…”
Section: Introductionmentioning
confidence: 99%